Social Value of Renewable Energy in Remote Northern Indigenous Communities - Lim, Anne; Poelzer, Greg; Noble, Bram (Journal of Aboriginal Economic Development, 2024)
Renewable energy (RE) is at the forefront of Canada’s strategy to achieve a net-zero electricity grid by 2035. The development of RE projects is also promoted as a means to deliver energy services in rural and remote Indigenous communities across the North. Although RE projects have the potential to contribute to sovereignty, self-sufficiency, and economic reconciliation, the social value of RE to Indigenous communities is often overlooked and poorly understood. This article advances themes for understanding and approaching RE developments to better assess their social value. It does so based on the analysis of lessons from RE research in northern Canada and Alaska. We demonstrate that RE projects can create outcomes that are value generating or value eroding and that such outcomes are often couched in the context of supporting or detracting from self-determination. Techno-human variables, from community vision and capacity to policy environments and local RE ownership, serve to enable or inhibit the realization of value-generating outcomes from RE. Finally, we identify several pathways to creation from RE, including relationships and collaborative leadership, knowledge and skills-development, Indigenous-led policies that decrease energy bureaucracy and manage benefits distribution, and regulations and structures that safeguard ecologies.